Amido rare-earth complexes supported by an ansa bis(amidinate) ligand with a rigid 1, 8-naphthalene linker: synthesis, structures and catalytic activity in rac-lactide polymerization and hydrophosphonylation of carbonyl compounds. (27th November 2014) - Yakovenko, Marina V.; Udilova, Natalia Yu.; Glukhova, Tatyana A.; Cherkasov, Anton V.; Fukin, Georgy K.; Trifonov, Alexander A.
Abstract : We report the synthesis of rare-earth amides and their catalytic activity in ROP of lactide. Abstract : A synthetic approach to rare-earth amido complexes coordinated by an ansa bis(amidinate) ligand with a 1, 8-naphthalene linker was developed and allowed for the synthesis of a series of complexes [1, 8-C10 H6 {NC( t Bu)N-2, 6-Me2 C6 H3 }2 ]LnN(SiMe3 )2 (THF) n (Ln = Y, n = 0 (2 ); Ln = Sm, n = 1 (3 ); Ln = Nd, n = 1 (4 )) in reasonable yields. Complexes2–4 initiate ring-opening polymerization (ROP) of rac -lactide and enable complete conversion of 100–250 equiv. of monomer within 60–90 min at 25 °C. The obtained polylactides feature atactic structures and moderate molecular-weight distributions ( M w / M n = 1.30–2.12). The experimental M n values of the obtained polymers are found to be significantly higher than the calculated ones due to a slow initiation stage. Effective immortal ROP of lactide with 3–5 equiv. of isopropanol per metal center was performed using complexes2–4 as the catalysts. The systems2–4 /iPrOH exhibit higher activities in ROP and allow for complete conversion of 100–300 equiv. of rac -lactide to polymer within 30–60 min at 25 °C and provide a living polymerization mode and very narrow polydispersities ( M w / M n = 1.13–1.27). Complexes2–4 as well as related borohydrides [1, 8-C10 H6 {NC( t Bu)N-2, 6-Me2 C6 H3 }2 ]Ln(BH4 )(μ-BH4 )Li(THF)2 (Ln = Sm, Nd) catalyze hydrophosphonylation of aldehydes at room temperature with good reaction rates and hydrophosphonylation of benzylideneacetone at 65 °C.